Decentrallisation as a means of conflict management: A case study of Kibaale District, Uganda - Anna Katharina Schelnberger (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2005)
The working paper contributes to the discussion of political instruments of conflict management by providing empirical evidence on decentralisation as a means of conflict management. The case study used in this paper is Kibaale District in Western Uganda. After independence migrants from southwestern Uganda settled in the sparsely populated district. They compete with the original population over the available land. In March 2002 Fred Ruremera – a member of the migrant community – was elected as the district chairman (head of local government). His election was not accepted by the original inhabitants and sparked ethnic conflict and widespread violence. Peace was only restored after the President of Uganda, Yoweri Museveni, intervened, Fred Ruremera agreed not to assume office and a compromise candidate was installed in his place. While positive impacts of decentralisation on conflict are expected because of the increased participation and the possibility of addressing local problems at the local level, negative impacts can stem from increased competition over resources and access to power. The paper identifies four general factors that determine whether decentralisation acts as a means of conflict management: the legal framework of the decentralisation policy, freedom from outside interventions into the workings of local government, the inclusiveness of local government and the type of conflict. The paper comes to the conclusion that – contrary to expectation – decentralisation and the increased participation have increased and created conflict rather than managed it. The reason lies mostly in the design of the decentralisation policy: The electoral system provides for the direct election of the chairman by plurality – not majority of the population and in the position of the district chairman power is actually re-centralised. Local government is also not sufficiently independent from central government, with constitutional clauses in case of a state of emergency allowing a high degree of control.
Keywords: 330; Dezentralisierung; Uganda; Politischer Konflikt